دراسة إحصائية لانتاجية العمل في بعض شركات الغزل و النسيج في سورية خلال الفترة 1994 - 2004 - العلي، إبراهيم محمد; ناصر، فراس عدنان; غزال، فايز (جامعة تشرين, 2005)
يعتبر العمل العنصر الفعال في العملية الإنتاجية والمحرك القوي لعجلة التطور الاقتصادي والاجتماعي على مر العصور، فالعمل هو نشاط الإنسان الجسدي والفكري الهادف والموجه لخلق الخيرات المادية وتقديم الخدمات الاجتماعية والثقافية بإنتاجية عالية لتحقيق هدف محدد في فترة معينة. إذا العنصر الإنساني في العمل هو أهم عناصر الإنتاج والاستثمار فيه يفوق الاستثمار في باقي العناصر. وفى هذا السياق جرى إعداد هذا البحث لمعالجة المشاكل التي تعترض العمال أثناء قيامهم بعملهم، لأن الأفراد لهم آمال ورغبات ودوافع تحكم سلوكهم، وهذا يؤثر بشكل مباشر على مستوى أدائهم وإنتاجيتهم، وذلك على عكس الوضع بالنسبة لعناصر الإنتاج الأخرى التي يمكن التحكم فيها بحسب ما نشاء، ونظراً للدور الكبير الذي يلعبه قطاع الغزل والنسيج في سورية في دعم الاقتصاد الوطني وفي رفد الموازنة العامة للدولة بموارد كبيرة. قمنا في هذه الدراسة بتحليل إنتاجية عامل الإنتاج في بعض شركات الغزل والنسيج في سورية بواسطة تحليل التباين، ولقد توصلنا على بعض النتائج نذكر أهمها وهي: 1-توجد فروقات جوهرية بين متوسطات إنتاجية عامل الإنتاج في مختلف الشركات المدروسة. 2-توجد فروقات جوهرية بين متوسطات إنتاجية عامل الإنتاج بين كل شركتين على حدة: (القطنية - التجارية الصناعية المتحدة/ الخماسية/)، (القطنية – النسيج)، (القطنية – الوليد). 3-لا توجد فروقات جوهرية بين متوسطات إنتاجية عامل الإنتاج بين كل شركتين على حدة: (التجارية الصناعية المتحدة/ الخماسية/ - السورية)، (التجارية الصناعية المتحدة/الخماسية/ - غزل جبلة)، (السورية - غزل جبلة). Labour represents an active element in the productivity operation and a strong supporter for both the economical and social development through many ages. Labour means human physical and mental activity that aims to fulfill financial interest, and to accomplish a high amount of social and cultural services to establish a definite purpose during limited time. So, the human element of working is the most important one in production. And human investments are greater than that of other elements. In this context, the research has been done to face problems that interrupt workers' activity, because their behaviour are affected by their hopes, desires and motives. Unlike other production elements that may be managed according to our needs, and because of the great role of by the Syrian textile sector in supporting the national economy and offering the budget huge resources, this thing affects directly the worker's productivity and performance rate. In this study we analyzed the workers' productivity of some Syrian textile companies by analyzing contrasts and differences between them. The results which have been reached are as follows: 1- There are substantial differences among workers, productivity average through studies o several companies. 2- There are basic disparities among workers productivity average between each two companies: (Cotton Company - United Commercial and Industrial Company), (Cotton Company - Textile Company), (Cotton Company -AL Walid Company). 3- There are no substantial differences among workers, productivity average between each two companies: (United Commercial and Industrial (Company - Syrian Company), (United Commercial and Industrial company -Textile company of Jablah), (Syrian company - textile company of Jablah).
Keywords: الإنتاجية -- شركات الغزل و النسيج -- الصناعة -- سورية -- الدراسات الإحصائية -- القوى العاملة -- الميزانية -- علم النفس الصناعي -- الفروق الفردية -- الأجور -- الرضا الوظيفي